2005
DOI: 10.1111/j.1460-9568.2005.04108.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidyl‐inositide signalling proteins in a novel class of sensory cells in the mammalian olfactory epithelium

Abstract: Ciliated sensory neurons, supporting cells and basal stem cells represent major cellular components of the main olfactory epithelium in mammals. Here we describe a novel class of sensory cells in the olfactory neuroepithelium. The cells express phospholipase C beta-2 (PLC beta2), transient receptor potential channels 6 (TRPC6) and inositol 3, 4, 5-trisphosphate receptors type III (InsP3R-III). Unlike ciliated olfactory neurons, they express neither olfactory marker protein nor centrin, adenylyl cyclase or cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(101 citation statements)
references
References 54 publications
4
96
1
Order By: Relevance
“…A TRP-like channel has been identified in physiological experiments in lobster OSNs (37), TRPC2 has been postulated to mediate chemical detection in the vomeronasal organ (12,14), and TRPC6 is found in a subset of odor-responsive cells in the olfactory epithelium (38). The TRPC6-expressing cells do not express OMP and are morphologically distinct from the OMP-expressing TRPM5 OSNs described here.…”
Section: Discussionmentioning
confidence: 99%
“…A TRP-like channel has been identified in physiological experiments in lobster OSNs (37), TRPC2 has been postulated to mediate chemical detection in the vomeronasal organ (12,14), and TRPC6 is found in a subset of odor-responsive cells in the olfactory epithelium (38). The TRPC6-expressing cells do not express OMP and are morphologically distinct from the OMP-expressing TRPM5 OSNs described here.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium influx through the CNG channel then results in the opening of calcium-gated chloride channels [70,117] Noncanonical pathway for olfactory signaling Although investigation of odorant response in Gaolf, ACIII, and CNGA2 knockout mice strongly suggested that cAMP played a crucial role in olfactory signal transduction [68,73,74], CNGA2-deficient mice retained a limited electro-olfactogram (EOG) response to some odorants [34]. Such residual responses were thought to be contributed by the atypical OSNs that express TRPM5 [75] or GC-D [76], or from the microvillar cells called Jourdan cells [77]. TRPM5 is a calcium channel located in cells expressing taste receptors, and is also expressed in a subset of OSNs that express CNGA2 [75].…”
Section: Olfactory Signal Transductionmentioning
confidence: 99%
“…The MOE and VNO have long been known to differ at the cellular level, with the receptors of each sensory system being expressed in ciliated or microvillar receptor neurons respectively, although a small sub-population of microvillar cells have been identified in the mouse MOE [27]. Like the vomeronasal receptors, the receptors of the MOE are G protein-coupled seven-transmembrane proteins, however they are evolutionarily distinct from both the V1Rs and V2Rs and can themselves be grouped into two separate gene families.…”
Section: The Main Olfactory System and Pheromonesmentioning
confidence: 99%